Social participation in the management of village funds in Sanleo village, East Malaka sub-district, Malaka regency - Melkianus Y Bere; Nursalam Nursalam; Hendrik Toda (goodwood publishing, 2020)
Purpose: This study describes and analyzes Social participation in Management of Village Fund in Sanleo village, East Malaka sub-district, Malaka regency. Research methodology: This study uses a descriptive research method with a qualitative approach. Social participation is analyzed using the views of Cohen and Uphoff (1977. Results: The results in this study are that the village society has been quite actively involved from the decision-making stage to enjoying the results. However, it is not even implemented at the evaluation stage, so the village government cannot confidently measure the success of a program being implemented. Limitations: This research only describes and analyzes social participation in the Management of Village Fund in Sanleo village, East Malaka sub-district, Malaka regency. Findings may differ in other areas. Contribution: This research becomes scientific information for public administration science.